2021
DOI: 10.3389/fpsyg.2021.661831
|View full text |Cite
|
Sign up to set email alerts
|

“We’re All in the Same Boat” – The Experience of People With Mental Health Conditions and Non-clinical Community Members in Integrated Arts-Based Groups

Abstract: In recent decades there has been a significant increase in community rehabilitation programs for people with mental health conditions. One such nationwide programs is Amitim in Israel whose mission is to foster the psychosocial rehabilitation of people with mental health conditions in the community. Amitim’s flagship program consists of arts-based groups that integrate participants with mental health conditions and non-clinical community members. To better understand the experiences of participants in these ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…It is noteworthy that these quantitative results are corroborated by our qualitative findings (Nitzan & Orkibi, 2021), where people with MHCs indicated that participation in the integrated arts-based groups not only enabled personal creation, emotional expression, and stress relief through the arts in a safe space, but also had a positive impact on their personal recovery processes including increases in self-efficacy, self-esteem, motivation for personal and interpersonal development, empowerment, and sense of belonging to the community. Overall, our results are also consistent with evidence that CSE is associated with adaptive outcomes such as well-being and creative adaptability (Orkibi et al, 2021), mental well-being (Fino & Sun, 2022), and even posttraumatic growth (Orkibi & Ram-Vlasov, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It is noteworthy that these quantitative results are corroborated by our qualitative findings (Nitzan & Orkibi, 2021), where people with MHCs indicated that participation in the integrated arts-based groups not only enabled personal creation, emotional expression, and stress relief through the arts in a safe space, but also had a positive impact on their personal recovery processes including increases in self-efficacy, self-esteem, motivation for personal and interpersonal development, empowerment, and sense of belonging to the community. Overall, our results are also consistent with evidence that CSE is associated with adaptive outcomes such as well-being and creative adaptability (Orkibi et al, 2021), mental well-being (Fino & Sun, 2022), and even posttraumatic growth (Orkibi & Ram-Vlasov, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…This study's significant pre-post intervention differences should be interpreted carefully considering the small sample, the self-reports, and the absence of a comparison group. A third study qualitatively showed the benefits of these arts-based groups, as mentioned above (Nitzan & Orkibi, 2021).…”
Section: The Amitim Programmentioning
confidence: 84%
See 3 more Smart Citations